2022
DOI: 10.1038/s41586-022-04638-9
|View full text |Cite
|
Sign up to set email alerts
|

CCNE1 amplification is synthetic lethal with PKMYT1 kinase inhibition

Abstract: Amplification of the CCNE1 locus on chromosome 19q12 is prevalent in multiple tumour types, particularly in high-grade serous ovarian cancer, uterine tumours and gastro-oesophageal cancers, where high cyclin E levels are associated with genome instability, whole-genome doubling and resistance to cytotoxic and targeted therapies1–4. To uncover therapeutic targets for tumours with CCNE1 amplification, we undertook genome-scale CRISPR–Cas9-based synthetic lethality screens in cellular models of CCNE1 amplificatio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
91
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 63 publications
2
91
0
Order By: Relevance
“…For instance, RB1 loss, which causes chromosome segregation errors, micronuclei, and DNA damage in different tumor models, induces sensitivity to targeted inhibitors of the mitotic regulators polo-like kinase 1 (PLK1) and Aurora kinase A/B ( 20 , 22 , 26 29 ). Moreover, Gallo et al ( 30 ) have demonstrated that CCNE1 overexpression, which can override the G 1 -S checkpoint and cause resistance to CDK4/6i, sensitizes cancer cells to PKMYT1 inhibition, causing cell death through premature entry into mitosis and mitotic catastrophe. A recent study by Crozier et al ( 31 ) demonstrated that short-term CDK4/6i treatment induced replication stress and genomic instability in immortalized RPE1 cells.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, RB1 loss, which causes chromosome segregation errors, micronuclei, and DNA damage in different tumor models, induces sensitivity to targeted inhibitors of the mitotic regulators polo-like kinase 1 (PLK1) and Aurora kinase A/B ( 20 , 22 , 26 29 ). Moreover, Gallo et al ( 30 ) have demonstrated that CCNE1 overexpression, which can override the G 1 -S checkpoint and cause resistance to CDK4/6i, sensitizes cancer cells to PKMYT1 inhibition, causing cell death through premature entry into mitosis and mitotic catastrophe. A recent study by Crozier et al ( 31 ) demonstrated that short-term CDK4/6i treatment induced replication stress and genomic instability in immortalized RPE1 cells.…”
Section: Introductionmentioning
confidence: 99%
“…The synthetic lethal relationship between CCNE1 amplification and the absence of PKMYT1 activity was confirmed both genetically and chemically (with RP-6306 ) through comparison of the growth sensitivity of isogenic fallopian tube cells (FT282 cells) engineered to overexpress CCNE1 relative to wild-type cells . Furthermore, multiple cancer cell lines and xenograft models with amplified CCNE1 or cyclin E over-expression showed greater growth inhibition compared to normal counterparts . Using a very sensitive and robust CCNE1 -amplified ovarian xenograft model (OVCAR3), we sought to understand the relationship between target inhibition, RP-6306 exposure, and efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…PKMYT1 function does not appear to be critical in the unperturbed cell cycle, whereas WEE1 function is essential for cell cycle progression of cells . However, the absence of functional PKMYT1 in a genetically vulnerable tumor, such as with CCNE1 amplification, causes cells to lose major checkpoint regulation leading to hyperactive CDK1, unscheduled mitosis and catastrophic DNA damage, ultimately resulting in cell death . No selective inhibitors have been previously reported for PKMYT1 that would allow for the investigation of the pharmacological activity.…”
Section: Introductionmentioning
confidence: 99%
“…For example, chr8q24.21 amplification was frequent in advanced GC [ 31 ], and involved in liver metastasis of rectal adenocarcinoma [ 32 ]. chr19q12 amplification was prevalent in multiple tumor types [ 33 ]. Consistently, in 65.8% of HAS cases there existed the amplification of chr19q12.…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, in 65.8% of HAS cases there existed the amplification of chr19q12. Amplification of the CCNE1 locus in this region was synthetic lethal related, targeted by PKMYT1 kinase inhibition, and it was also a promising target in AFPGC, which warranted further research in HAS [ 10 , 33 ]. Deleted regions-associated studies were mainly involved in gastrointestinal defects, Peutz-Jeghers syndrome (19p13.3), and immunodeficiency (14q32.33) [ 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%